AB1183 Joint Operations as an Indicator of Disease Severity and Burden in the Quest-RA Study. (9th June 2015) - Sokka, T.; Khan, N.; Nikiphorou, E.; Verstappen, S.; Hetland, M.; Inanc, N.; Laurindo, I.; Stropuviene, S.; Combe, B.; Cutolo, M.; Jacobs, J.
Abstract : Background: Joint replacement surgery represents a remarkable mile stone in the care of patients with rheumatoid arthritis (RA), aimed at improving patients' functional capacity and reducing pain. Prior to current therapeutic strategies, surgical joint intervention was a frequent event. Currently, orthopedic surgery is considered as a surrogate marker of failed medical treatment and joint destruction. Objectives: To compare disease burden in RA patients with and without major joint operation (MJO) in the QUEST-RA study. Methods: Consecutive unselected patients with RA receiving usual rheumatology care were included in QUEST-RA study between 2005 and 2012 in 107 clinics in 34 countries (16 with low and 18 with high Gross Domestic Product, GDP, cut at 20, 000$/person at the year of enrollment). The review included history of MJO: total joint replacement or fusion of hips, knees, shoulders, elbows, ankles, wrists, and the atlantoaxial joint. Clinical data at the cross sectional visit included disease activity based on DAS28(ESR, 3 variables) and patient reported outcomes (PROs) for disease burden (pain, global health, fatigue on 0-10cm VAS and HAQ on 0-3). Mean values of these variables were compared using parametric statistics in patients with or without history of MJO, according to disease duration (5-10 vs. >10 years), adjusted for age and sex, in countries with low vs. high GDP. Results: QUEST-RA includes 10, 142 patients; joint operation data were available in 9069 patients (81%Female, mean age 55, median disease duration from symptom-onset 12 years, 74% RF+). Proportion of RA patients with a history of MJO was more than two times in high GDP countries [12.9% (663/5158)] compared to low GDP countries [5.8% (227/3911)] despite the latter having higher disease activity and worse PROs. Disease burden was higher in patients with a history of MJO across the groups (Table ) except in patients with shorter disease duration 5-10 years in low GDP countries (all comparisons p=ns, data not shown). Conclusions: In the real world setting in 2005-2012, history of MJO in patients with RA indicated higher disease burden and severity compared to patients without MJO. Disclosure of Interest: None declared